Advice Method: KH Raden Asnawi's Offer for Islamic Education in the Family Environment - Nur Rizqiyah Al Karimah; Maragustam Siregar; Sembodo Ardi Widodo (International Journal Ihya' 'Ulum al-Din, 2024)
The family as an educational environment supports school and society education. This research is included in a qualitative approach and the library research category. This research aims to discover KH Raden Asnawi’s thoughts regarding appropriate methods in Islamic education in the family environment. Data was collected using documentation techniques, and data analysis used descriptive-analytic techniques. The analysis steps are data reduction, data presentation, and conclusion. The results of this research concluded that, according to KH. Raden Asnawi, there is one method that can be used in education in the family environment, namely the advice method. This method is used to instill mahmudah morals in the form of tawadhu and muhasabah and to distance them from madzmumah morals in the form of being arrogant.